A Study of Elementary Level English as Foreign Language Students’ Attitudes towards Reading for Pleasure in English at Bangkok Christian International School, Thailand - Lwin, Zarni; Lynch, Richard (Scholar: Human Sciences, 2016)
The purpose of this study was to investigate if there is a significant positive relationship between the attitudes towards reading for pleasure in English and their academic achievement of elementary level students of English as a foreign language (EFL) at Bangkok Christian International School (BCIS), Thailand. One hundred and seven elementary level students of BCIS participated in this study in the first semester of the 2012-2013 academic year. The quantitative data acquired from the questionnaire indicated that the participants had positive attitude towards reading for pleasure in English. The data also revealed the two main barriers for the students to read for pleasure in English. First, the students had difficulty choosing/finding books that interested them. Second, they had a lack of time to read for pleasure in English. The results also indicated that there were two distinct motivation factors. Intrinsically, the students would read if better/more books were available in the library. Extrinsically, the students would read if reading would help their grades improve. There was no indication of grade or gender differences in motivation to read for pleasure. However, there was a significant positive relationship between the students’ attitudes towards reading for pleasure and their academic achievement.